The Authoritativeness of Fatwa: A Study of Sharia Banks' Compliance with the DSN-MUI Fatwa on Fund-Raising - Abdul Mun'im Saleh; Rizqi Jauharotul Amalia; Khoirul Fathoni (Justicia Islamica, 2023)
This article investigates the background of Bank SS Syariah Jatituwo Branch Office's decision to launch the Protab program, which conflicts with Fatwa No. 86/DSN-MUI/XII/2012 of the Indonesian Ulema Council (DSN-MUI) concerning Gifts in Fundraising for Islamic Financial Institutions. The decision in the case of Bank SS Syariah Jatituwo raises questions about the DSN-MUI Fatwa's binding power over Islamic financial institutions in Indonesia. The information in this research gathered from the leaders and officials of Bank SS Syariah Jatituwo was analyzed using the theory of fatwa in Islamic legal thought and the role of the DSN-MUI Fatwa in the Indonesian national legal system. This study concludes that the position of a non-binding fatwa is correct according to Islamic law. This, however, violates the direction of positive law in Indonesia, which in principle gives the DSN-MUI Fatwa binding power and requires Bank Indonesia to transform the material for the DSN-MUI Fatwa, which contains sharia principles regarding sharia economy and finance, into material content of statutory regulations. have legal and binding force. Because these requirements have not been made the standard in laws and regulations and have only been appointed in concept, the Director of Bank SS Syariah Jatituwo uses loopholes to disagree with fatwas and laws.